2020
DOI: 10.1021/jacs.0c07276
|View full text |Cite
|
Sign up to set email alerts
|

Discovery and Optimization of Small-Molecule Ligands for V-Domain Ig Suppressor of T-Cell Activation (VISTA)

Abstract: V-domain Ig suppressor of T-cell activation (VISTA) is an immune checkpoint that affects the ability of T-cells to attack tumors. A FRET-based high throughput screening identified NSC622608 as the first small-molecule ligand for VISTA. Investigation of the interaction of NSC622608 with VISTA using STD NMR and molecular modeling enabled the identification of a potential binding site in VISTA for NSC622608. Screening NSC622608 against a library of single-point VISTA mutants revealed the key residues in VISTA int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 26 publications
0
17
0
Order By: Relevance
“…In this study, CA-170 enhanced T cell immune responses and the production of IFN-γ [ 52 ]. CA-170 is in clinical development; however, a recent study showed minimal to no binding of CA-170 to human VISTA by time-resolved fluorescence energy-transfer assay [ 53 ]. In this study, another small-molecule inhibitor, compound III, inhibited VISTA immunosuppressive function, as measured by increased IFN-γ and TNF-α secretion by Jurkat T cells cocultured with VISTA-positive ovarian cancer cell lines.…”
Section: Vista In the Context Of Immunotherapymentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, CA-170 enhanced T cell immune responses and the production of IFN-γ [ 52 ]. CA-170 is in clinical development; however, a recent study showed minimal to no binding of CA-170 to human VISTA by time-resolved fluorescence energy-transfer assay [ 53 ]. In this study, another small-molecule inhibitor, compound III, inhibited VISTA immunosuppressive function, as measured by increased IFN-γ and TNF-α secretion by Jurkat T cells cocultured with VISTA-positive ovarian cancer cell lines.…”
Section: Vista In the Context Of Immunotherapymentioning
confidence: 99%
“…In this study, another small-molecule inhibitor, compound III, inhibited VISTA immunosuppressive function, as measured by increased IFN-γ and TNF-α secretion by Jurkat T cells cocultured with VISTA-positive ovarian cancer cell lines. Docking and mutational analysis showed that compound III interacted with VISTA residues F94, R159, and E157, with a strong hydrophobic interaction with Y69 and H153 [ 53 ]. Thus, small-molecule inhibitors are under development as putative VISTA therapeutics in addition to antagonist and agonist antibodies.…”
Section: Vista In the Context Of Immunotherapymentioning
confidence: 99%
“…Additionally, such compounds’ structures can be easily optimized to get the desired biological activity. Previously, only Li et al (2020) and Gabr and Gambhir (2020) reported small-molecule inhibitors against VISTA. Thus, lead-like natural compounds from MPD3 were retrieved ( Figure 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…There are two proved ligands of VISTA, one is IGSF11, the other is PSGL1 (P-selectin glycoprotein ligand 1) [ 13 , 14 ]. Besides these, VSIG8, NSC622608 and Galectin 9 may be potential ligands for VISTA [ 15 , 16 ]. The interaction between ligands and receptors may be modulated by the pH in microenvironment [ 14 ], and exert innate and adaptive immune regulation [ 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%